Kritik Fath al- Dharī’ah Terhadap Fatwa Majma’ al- Buḥūṭ al- Islāmiyyah bi al- Azhar Tentang Larangan Perkawinan Kembar Siam (Studi Kembar Siam Tipe Craniopagus) - Muhammad Alwi al Maliki; Ahmad Adharul Ja'fari; Asep Saepudin Jahar (Asy-Syari’ah : Jurnal Hukum Islam, 2023)
This article examines the fatwa of Majma 'al-Buḥuṭ al-Islāmiyyah bi al-Azhar regarding the prohibition of conjoined twin marriages. In the Fatwa, stated that conjoined twin marriages are invalid because it is similar to gathering two sisters in one covenant and giving rise to mafsadah in the form of negative things that arise in marriage. The main data in this study are fatwa al-Azhar on the prohibition of conjoined twin marriage and several documents and literature on conjoined twins. Secondary data in the form of some literature that supports the research theme. The analytical method used is a descriptive-analytical method using the theory of fath al-dharī'ah as a knife of analysis. Based on research results, not all conjoined twins are prevented from getting married. As in the case of craniopagus type conjoined twins. Some negative things as expected by the al-Azhar fatwa can be overcome by this type of conjoined twins. Based on the theory of fath al-dharī'ah, if the greater benefit can be realized, then the prohibition provisions can be allowed. Artikel ini mengkaji fatwa Majma’ al- Buḥuṭ al- Islāmiyyah bi al- Azhar tentang larangan perkawinan kembar siam. Dalam Fatwa tersebut dinyatakan bahwa perkawinan kembar siam secara mutlak tidak sah karena sama halnya dengan mengumpulkan dua saudara dalam satu akad serta menimbulkan mafsadah berupa hal-hal negatif yang timbul dalam perkawinan. Data utama dalam penelitian ini berupa fatwa al- Azhar tentang larangan perkawinan kembar siam dan beberapa dokumen serta literatur tentang kembar siam. Data sekunder berupa beberapa literatur yang menunjang tema penelitian. Metode analisis yang dipakai berupa metode deskripstif-analitis dengan menggunakan teori fath al- dharī’ah sebagai pisau analisis. Berdasarkan hasil penelitian, tidak semua kembar siam terhalang untuk menikah. Seperti dalam kasus kembar siam tipe craniopagus. Beberapa hal-hal negatif sebagaimana yang diduga oleh lembaga fatwa al- Azhar dapat diatasi oleh kembar siam tipe ini. Berdasarkan teori fath al- dharī’ah, apabila kemaslahatan yang lebih besar dapat terealisasi, maka ketentuan yang semula dilarang menjadi diperbolehkan.